An investigation of secondary electron emission from ZnO based nanomaterials for future applications in radiation detectors - P. Boutachkov (Nature Portfolio, 2021)
Abstract This paper discusses the use of nanomaterials for the improved performance of time-of-flight particle detectors based on secondary electron emission (SEE). The purpose of the research presented in this paper is to find a nanomaterial that has a higher SEE than gold. In this article, we present a measurement of the SEE properties from 1D (one-dimensional) nanostructures of ZnO and ZnO/GaN (ZnO with GaN coating) composed of a mostly regular pattern of nanotubes grown on a thin Si3N4 substrate. The study was performed with 4.77 meV/u Au beam. We observed an average increase of 2.5 in the SEE properties from the 1D ZnO nanotubes compared to gold.